Traumatic Occlusion of the Middle Cerebral Artery - Kumar, Sushil; Desai, Ashish; Tiwary, Ravi; Garg, Amit (Indian Journal of Neurotrauma, 2015)
Traumatic occlusion of the middle cerebral artery (MCA) is very rare compared to occlusion of the internal carotid and basilar artery. Patients with longer latency have lower mortality. Herein, we report two cases of MCA occlusion who deteriorated under observation because of MCA territory infarction. CT angiography revealed occlusion of MCA in M1 segment. Both were subjected to decompressive craniotomy. First patient is ambulatory and has spastic gait. Second patient showed improvement in sensorium and still requires nursing care.
Keywords: posttraumatic occlusion; posttraumatic thrombosis; middle cerebral artery; decompressive craniectomy